Socio-educational competencies required for teachers of students with autism spectrum disorder: Parents' perspective - M. A. Sakarneh; A. H. Ziadat; A. A. Almakahleh; M. A. Rababah; A. H. Alhassan; L. A. Al-Muhairat; H. A. Al-Rababah (Russian State Vocational Pedagogical University, 2023)
Introduction. Autism spectrum disorder (ASD) is among the widely spreading disorders across the globe. Professionals in educational, sociological, and medical fields continuously investigate the effective ways to deal with individuals having ASD because they cannot be dealt in a similar way as others rather teachers have to immerse them in regular classes. Therefore, teachers should have sufficient training and developed competencies to deal with students with ASD Aim. This study aims to explore the extent to which teachers of students with ASD possess of the cognitive competencies and skills necessary from the perspectives of students' parents.Methodology and research methods. A quantitative method was adopted to analyse the data. The study sample included 45 parents. The tool used is a checklist of the socio-educational competencies needed for teachers of students with ASD developed by Mehidat et al. (2014). It consisted of 40 items, which determine the response rating scale for the estimation of parents' perception about the importance of socio-educational competencies needed for teachers.Results. The results showed that the parents' estimation of teachers' possession of socio-education-al competencies needed for teachers of students with ASD was average.Theoretical significance. The current study contributes in enriching related literature as well as it may practically help in identifying the required competencies and highlighting the importance of teachers' possession of socio-educational competencies and skills to deal with students having ASD. So, the study helps educationists, policy-makers and most importantly teachers to focus on these important competencies and skills and work on learning them, and eventually can enhance the learning of students with ASD. As the study focuses on parents' perspective, it has a significant contribution in enhancing quality of education being provided to students with ASD and making them constructive individuals by enhancing their learning, because parents can evaluate the effect of these competencies and they can provide the best and most effective feedback.Practical significance. There are different aspects of cognitive competencies and skills necessary for teachers of students with ASD to be addressed by special education stakeholders and policy-makers in the field of special education, particularly teaching children with autism spectrum disorders, when they consider and develop pre-service and in-service programmes for teachers of students with ASD. Most importantly, there is a dire need to develop awareness among teachers about the importance of their personal development for enhancing certain competencies and skills to enable them to identify autistic students and effectively deal with them to enhance their learning as well.